Pengaruh Pemahaman Tentang Riba dan Bagi Hasil Terhadap Keputusan Menabung di BNI Syariah Surabaya - Mahmuda, Rifaatul; Anwar, Moch. Khoirul (Universitas Negeri Surabaya, 2019)
This study aims to examine the effect of understanding usury and profit sharing on the decision of customers' savings at BNI Syariah Surabaya Branch Office. This research was conducted by using a quantitative approach. The number of samples used in this study were 100 Muslim respondents who were taken from customers by using questionnaires measured through a test scale and likert and analyzed by using SPSS program assistance. The results of this study indicate that partially understanding of usury does not have a significant effect on the on the decision of customers' savings. Based on the T test that has been conducted shows that the understanding of profit sharing has a significant effect on the decision of customers' savings. According to R square test, usury and understanding of profit sharing have a percentage effect up to 8.9% on saving decision.